5.2/5.7-GHz 48-dB image rejection GaInP/GaAs HBT weaver down-converter using LO frequency quadrupler - Wu, Tzung-Han; Meng, Chinchun (My University, 2006)
A GaInP/GaAs heterojunction bipolar transistor (HBT) down-converter using the Weaver architecture is demonstrated in this paper. The Weaver system is a double-conversion image rejection heterodyne, system which requires no bandpass filters in the signal path and no quadrature networks. The Weaver down-converter has the image rejection ratios of 48 dB and 44 dB when the RF frequency is 5.2 GHz and 5.7 GHz, respectively. A new frequency quadrupler is employed in the down-converter to generate the local oscillator (LO) signals. The frequency quadrupler is designed to minimize the phase error when generating LO signals and thus the image rejection performance is improved. A diagrammatic explanation using the complex mixing technique to analyze the image rejection mechanism of the Weaver architecture is developed in this paper. From our analysis, the image rejection can be further improved by making the LO1 and LO2 signals coherent.
Keywords: complex mixing technique; frequency quadrupler; Gilbert mixer; image rejection; Weaver architecture